Update on feline alphaherpesvirus‐1 seroprevalence in Victorian feral and owned cats. Issue 5 (25th January 2022) - Cottingham, E; Johnstone, T; Hartley, CA; Devlin, JM
Abstract : The seroprevalence of feline alphaherpesvirus‐1 (FHV‐1) in feral cats in Victoria, Australia, was last assessed in 1981 when serum‐virus‐neutralising antibodies (VNAb) against FHV‐1 were detected in 11% of the sampled population from two Victorian locations. In this current study, VNAb were assessed in serum from feral cats located in Phillip Island, Point Cook and Hattah in the Mallee region in Northern Victoria. In feral cats, the seroprevalence of VNAb to FHV‐1 was highest in Point Cook at 24.6% (17/69), followed by Phillip Island at 16.7% (11/66) and Hattah where no feral cats had detectable VNAb to FHV‐1 (0/12). In contrast, virus‐neutralising antibodies were observed in 84.1% (37/44) of Victorian‐owned cats. This higher seroprevalence in owned cats is likely due to the use of FHV‐1 vaccines; however, the vaccination history of the cats was not known and the development of neutralising antibodies after infection or vaccination can vary. The results are useful for understanding FHV‐1 exposure in feral and owned cats and are important background information in the context of any potential future use of FHV‐1‐vectored vaccines.